Metaphor and Symbol in Madurese Proverb: A Study of Madurese Characters - Supardi, Moh; Merdeka, Pita (Insaniyat : Journal of Islam and Humanities, 2025)
The pervasive meaning and the representative symbol of metaphors have led different views among scholars. Contemporary view has claimed that metaphor is basically symbolic in nature and is pervasive in human language, mind, and culture that goes beyond the scope of a language rather than just as language ornament conceived by the traditional view. The present study is close to the first view that metaphor and symbol in Madurese proverbs are not only matters of language but they mostly take into account with human way of thinking. Moreover, this study also takes a stand that metaphors and symbols can affect social thought and characters. In these regards, constructing the abstract meaning of metaphors - grounded in human mind and culture - has made visible need for this study to use Socio-Cognitive Linguistic approach. It is worth to use such integrated approach to see metaphoric and symbolic meaning about the nature of interpretation reflected in Madurese proverbs to reveal Madurese characters. The study showed that Madurese proverbs have reflected the courageous, religious, humorous, self-reliant, persistent and hard work, direct, and innocent characters of Madurese through their proverbial or metaphorical expressions. The study concluded that metaphors and symbols have played significant roles to reflect social markers due to the symbolic function and abstract meaning of metaphor is bond with human mind, experience, and culture structured through symbolic and metaphoric use.